Desain Pembelajaran Materi Peluang Berbasis PMRI Menggunakan Konteks Wisata Lokal - Fitriyana, Nur; Zulkardi, Zulkardi; Putri, Ratu ilma Indah; Susanti, Ely; Mulyono, Budi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a learning design based on the Indonesian Realistic Mathematics Education (PMRI) approach for teaching probability using the local context of Belitar Seberang Waterfall, Rejang Lebong Regency. The method employed is design research of the validation study type, which consists of three phases: preparing for the experiment, teaching experiment, and retrospective analysis. The teaching experiment was carried out in two stages: a pilot experiment involving six students and the main teaching experiment involving 23 eighth-grade students. Data collection techniques included Student Activity Sheets (LAS), observation, interviews, and documentation. The results show that 80% of students demonstrated a comprehensive understanding of probability concepts and experienced improved learning outcomes after participating in the PMRI-based learning. Revisions to the LAS during the pilot experiment had a positive impact on students’ conceptual understanding. Overall, the PMRI approach, grounded in a local context, proved effective in enhancing student engagement and understanding of mathematical concepts. Keywords: Learning Design, Hypothetical Learning Trajectory (HLT), PMRI, Probability, Tourism Context